Açaì (Euterpe oleracea) Extract Protects Human Erythrocytes from Age-Related Oxidative Stress - Alessia Remigante; Sara Spinelli; Elisabetta Straface; Lucrezia Gambardella; Daniele Caruso; Giuseppe Falliti; Silvia Dossena; Angela Marino; Rossana Morabito (Cells, 2022)
Aging is a process characterised by a general decline in physiological functions. The high bioavailability of reactive oxygen species (ROS) plays an important role in the aging rate. Due to the close relationship between aging and oxidative stress (OS), functional foods rich in flavonoids are excellent candidates to counteract age-related changes. This study aimed to verify the protective role of Açaì extract in a d-Galactose (d-Gal)-induced model of aging in human erythrocytes. Markers of OS, including ROS production, thiobarbituric acid reactive substances (TBARS) levels, oxidation of protein sulfhydryl groups, as well as the anion exchange capability through Band 3 protein (B3p) and glycated haemoglobin (A1c) have been analysed in erythrocytes treated with d-Gal for 24 h, with or without pre-incubation for 1 h with 0.5–10 µg/mL Açaì extract. Our results show that the extract avoided the formation of acanthocytes and leptocytes observed after exposure to 50 and 100 mM d-Gal, respectively, prevented d-Gal-induced OS damage, and restored alterations in the distribution of B3p and CD47 proteins. Interestingly, d-Gal exposure was associated with an acceleration of the rate constant of SO42− uptake through B3p, as well as A1c formation. Both alterations have been attenuated by pre-treatment with the Açaì extract. These findings contribute to clarify the aging mechanisms in human erythrocytes and propose functional foods rich in flavonoids as natural antioxidants for the treatment and prevention of OS-related disease conditions.